Passive transfer of SARS‐CoV‐2 antibodies with platelet transfusions. Issue 4 (26th February 2022) - Ramirez, Guillermo A.; Gautam‐Goyal, Pranisha; Shariatmadar, Sherry; Khatri, Akshay; McCann‐Pineo, Molly; Rasul, Rehana; Karkenny, Gabriel; Chang, Tylis; Sfakianos, Maria; Cassiere, Hugh; Epstein, Marcia
Abstract: Background: Although over 5000 platelet transfusions occur daily in the United States, the presence of SARS‐CoV‐2 antibodies in platelet units is not commonly evaluated for. The effects of platelet transfusions with SARS‐CoV‐2 antibodies remain largely unknown. We evaluated single‐donor (apheresis) platelet units for SARS‐CoV‐2 antibodies and determined if platelet transfusions passively transferred antibodies to seronegative recipients. Study Design and Methods: We conducted a retrospective analysis as part of a quality assurance initiative during February to March 2021 at a tertiary referral academic center in suburban New York. Platelet units and platelet recipients were evaluated for the presence of SARS‐CoV‐2 antibodies using the DiaSorin LIASON SARS‐CoV‐2 S1/S2 IgG assay. There were 47 platelet recipients eligible for study inclusion. The primary outcome was the presence of SARS‐CoV‐2 spike protein IgG antibodies in the recipient's blood after platelet transfusion. Results: Twenty‐three patients received platelets with SARS‐CoV‐2 spike protein IgG antibodies; 13 recipients had detection of SARS‐COV‐2 antibodies (56.5%), and 10 recipients did not. The median antibody titer in the platelet units given to the group with passive antibodies detected was significantly higher compared to the median antibody titer in the platelet units given to the group without antibodies detected (median [interquartile range]: 306 AU/ml [132, 400] vs. 96.1 AU/ml [30.6, 186], p = .027). Conclusions: Our study demonstrated a significant rate of passive transfer of SARS‐CoV‐2 spike protein IgG antibodies through platelet transfusions. Considering the volume of daily platelet transfusions, this is something all clinicians should be aware of.